The Explication of Margaret Drabble’s Feminist Ideas Against the Background of the Confrontation of Two Thinking Models (on the basis of the novel “The Millstone”) - Salamova, Azıza Sahıb (Advances in Social Sciences Research Journal, 2016)
The works of Margaret Drabble, who is considered one of the outstanding representatives of contemporary British feminist, is appraised as the manifesto of the feminist ideas. In her works M.Drabble addresses the problems of the society she lives in through her own identity and guides her creative identity to writing novels that urge one to think and make a choice. The writer has succeeded in presenting the ideas of feminism from the standpoint of “gender simmetry” and raised the problems of women and society, women and community. M.Drabble formulates her protest against the discrimination between woman and man by appealing to the restriction of female freedom. Her characters are courageous women who can act as a role-model in women’s struggle for choice - to live the life they want and decide on their own life. As a woman, spouse, mother, working woman, M.Drabble clearly realizes the impact of the burden laden on “the weaker gender” in all stages of women’s life and the stereotypes of behaviour dictated by social dominance and manages to act as “the mediator” for women, first of all, herself and her contemporaries by observing the complications led by the gender asymmetry. The heroine of the novel “Millstone” is the manifestation of the writer’s visions and the description of her confidence in a modern woman. M.Drabble manages to describe the image of a modern woman in the most convincing details and in full accuracy by coming round her heroine’s life out of her own. The analysis of M.Drabble’s novel “Millstone” brings to the reader’s judgement most austerely and boldly the two confrontations peculiar to her works. The problem raised in the work consists of the confrontation of the woman’s motherhood and spousehood which almost make “the neat line” of Drabble’s novels. The novel “Millstone” reveals most vividly the ideational-philosophical reality formed resulting from the XX-century feminist ideas, the women’s discarding their aspiration towards marriage as the number one indicator of their life success as “the aftereffects” of the alienation trends of gender stereotypes. This work is the successful solution from the perspective of describing the difficult path of a modern British woman’s recognition of her real power and realization of her psycho-social identity quite adequetely.